Algebraic generation of single domain computational grid for twin screw machines Part II – Validation. (July 2017) - Kovacevic, Ahmed; Rane, Sham
Highlights: New developed grid for twin screw machines presented in Part I of the paper has been tested. Grids with interlobe region refinement and single domain structure for both rotors are evaluated. Results have been validated with measurements of internal pressure, power, flow and efficiency. Significant improvement in performance prediction achieved by single domain computational grid. Fully hexahedral cell structure, improved grid quality, oil injection flow modelling achievable. Abstract: Algebraic procedures are available to generate computational grid for CFD analysis of twin screw compressors. Recently new algebraic method was formulated to generate numerical grids for CFD calculation of twin screw machines with grids generated from outer casing boundaries [16, 18]. In this paper, the grids of Rotor to Casing and Casing to Rotor type are tested for performance calculation of a dry air screw compressor using ANSYS CFX solver and the results have been compared with measurements. Firstly the base-line grid of the Rotor to Casing grid type was used to obtain CFD results. A grid independent solution was obtained for this base-line grid. The size of the mesh thus obtained has been used with other grid variants for comparison. A set of successively refined Casing to Rotor grid type was tested by increasing the density of nodes on the rotor profile in the interlobe leakage region. A gradual improvement in the accuracy of flow prediction was achieved with successive refinement in the interlobe region. The third variant used for comparison is a Casing to Rotor grid type with a single rotor domain that has no interface between the rotor blocks. A significant improvement in the prediction of flow and internal pressure was achieved. These developments have also extended the capability of the deforming grids to be used with other CFD solvers like STAR-CCM+ and ANSYS FLUENT. Due to fully hexahedral cell structure and improved global grid quality, addition of physical phenomena like oil injection in the models has now become achievable.